The complement system in innate and adaptive immunity: normal functioning of the complement system - Sacks, Steven (Henry Stewart Talks, 2021)
Complement system, C3 as the central component of the complement, Pattern recognition, Complement control proteins, Sites of complement synthesis, Innate and adaptive immune response